Selective targeting of pro-inflammatory Th1 cells by microRNA-148a-specific antagomirs in vivo. (May 2018) - Maschmeyer, Patrick; Petkau, Georg; Siracusa, Francesco; Zimmermann, Jakob; Zügel, Franziska; Kühl, Anja Andrea; Lehmann, Katrin; Schimmelpfennig, Sarah; Weber, Melanie; Haftmann, Claudia; Riedel, René; Bardua, Markus; et al.
Abstract: In T lymphocytes, expression of miR-148a is induced by T-bet and Twist1, and is specific for pro-inflammatory Th1 cells. In these cells, miR-148a inhibits the expression of the pro-apoptotic protein Bim and promotes their survival. Here we use sequence-specific cholesterol-modified oligonucleotides against miR-148a (antagomir-148a) for the selective elimination of pro-inflammatory Th1 cells in vivo . In the murine model of transfer colitis, antagomir-148a treatment reduced the number of pro-inflammatory Th1 cells in the colon of colitic mice by 50% and inhibited miR-148a expression by 71% in the remaining Th1 cells. Expression of Bim protein in colonic Th1 cells was increased. Antagomir-148a-mediated reduction of Th1 cells resulted in a significant amelioration of colitis. The effect of antagomir-148a was selective for chronic inflammation. Antigen-specific memory Th cells that were generated by an acute immune reaction to nitrophenylacetyl-coupled chicken gamma globulin (NP-CGG) were not affected by treatment with antagomir-148a, both during the effector and the memory phase. In addition, antibody titers to NP-CGG were not altered. Thus, antagomir-148a might qualify as an effective drug to selectively deplete pro-inflammatory Th1 cells of chronic inflammation without affecting the protective immunological memory. Highlights: Th1 cells expressing miR-148a mediate colitis in a murine model of IBD. Antagomir-148a inhibits colitis by selectively depleting Th1 cells from the colon. Antagomir-148a does not affect the protective immunological memory.